2013
DOI: 10.2337/dc14-s120
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Therapy Recommendations for the Management of Adults With Diabetes

Abstract: A healthful eating pattern, regular physical activity, and often pharmacotherapy are key components of diabetes management. For many individuals with diabetes, the most challenging part of the treatment plan is determining what to eat. It is the position of the American Diabetes Association (ADA) that there is not a "one-size-fits-all" eating pattern for individuals with diabetes. The ADA also recognizes the integral role of nutrition therapy in overall diabetes management and has historically recommended that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
485
5
21

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 661 publications
(518 citation statements)
references
References 222 publications
7
485
5
21
Order By: Relevance
“…The characteristics of this group were different from those participating in the quantitative research: 73% (29) were white, 63% (25) were female, 75% (30) were aged under 60 years of age, 53% (21) came from a deprived area in Leeds, and 68% (27) did not report a disability.…”
Section: Qualitative Analysesmentioning
confidence: 91%
“…The characteristics of this group were different from those participating in the quantitative research: 73% (29) were white, 63% (25) were female, 75% (30) were aged under 60 years of age, 53% (21) came from a deprived area in Leeds, and 68% (27) did not report a disability.…”
Section: Qualitative Analysesmentioning
confidence: 91%
“…Dietary salt restriction has been noted as an essential constituent of diabetes care in many guidelines,4, 5, 6, 7 although supportive evidence is apt to depend on studies of participants without diabetes or small short‐term studies of patients with diabetes. On the other hand, some longitudinal studies were recently reported regarding the association between dietary salt intake and diabetes complications in patients with diabetes 8, 9, 10.…”
Section: Resultsmentioning
confidence: 99%
“…In guidelines for the treatment for diabetes in various countries, medical nutritional therapy is described with an individual chapter, explaining recommendations for macronutrient intake including carbohydrate, protein, and fat and micronutrient intake as typified by salt. Table 1 summarizes recommendations for dietary salt intake by the American Diabetes Association (ADA)5 and European Association for the Study of Diabetes (EASD),6 which lead in the treatment of diabetes in the United States and Europe, and that of the Japan Diabetes Society (JDS) 4. The current goals for daily intake of dietary salt in ADA guidelines are below 5.84 g/d5 and 6 g/d in EASD guidelines 6.…”
Section: What Are the Current Status And Issues Of Leading Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations